Can biofeedback make you a better runner? - Crowther, G. (2001)
A technique known as biofeedback - one of the few topics in sports psychology that has been addressed with good research relevant to distance runners - is discussed. (This article originally appeared in the April 2001 issue of Northwest Runnermagazine.)